Silent neonatal influenza A virus infection primes systemic antimicrobial immunity - Heinemann, Anna Sophie; Stalp, Jan Lennart; Bonifacio, João Pedro Pereira; Silva, Filo; Willers, Maike; Heckmann, Julia; Fehlhaber, Beate; Völlger, Lena; Raafat, Dina; Normann, Nicole; Klos, Andreas; Hansen, Gesine; et al. (Frontiers in Immunology, 2023)
Infections with influenza A viruses (IAV) cause seasonal epidemics and global pandemics. The majority of these infections remain asymptomatic, especially among children below five years of age. Importantly, this is a time, when immunological imprinting takes place. Whether early-life infections with IAV affect the development of antimicrobial immunity is unknown. Using a preclinical mouse model, we demonstrate here that silent neonatal influenza infections have a remote beneficial impact on the later control of systemic juvenile-onset and adult-onset infections with an unrelated pathogen, Staphylococcus aureus, due to improved pathogen clearance and clinical resolution. Strategic vaccination with a live attenuated IAV vaccine elicited a similar protection phenotype. Mechanistically, the IAV priming effect primarily targets antimicrobial functions of the developing innate immune system including increased antimicrobial plasma activity and enhanced phagocyte functions and antigen-presenting properties at mucosal sites. Our results suggest a long-term benefit from an exposure to IAV during the neonatal phase, which might be exploited by strategic vaccination against influenza early in life to enforce the host’s resistance to later bacterial infections.